A hue for you a campaign that tackles and reexamines gender stereotypes through a children's clothing line without the use of gender categorization - Bautista, Fern Bernadette G.; San Valentin, Marc (Quezon City College of Fine Arts, University of the Philippines Diliman, 2018)
In today's society where rigid gender roles are slowly being broken down, gender stereotypes serve as hurdles to these efforts. Gender stereotypes tend to oversimplify and limit people when it comes to their traits and abilities. They remain a large contributor to gender inequality in society. Many Filipino parents nowadays are more accepting of new gender concepts and the people who practice these concepts, but remain hesitant when it comes to their own children. This is due o gender stereotypes that are ingrained n our society, with many Filipinos still subscribing ti them, both consciously and unconsciously. this thesis aims to tackle these gender stereotypes by targeting young children and their parents. My research has shown that teaching children at young age about gender can be beneficial for them for when they grow up and experience the world around them. Using clothes and colors as a way to teach young children about gender can be effective because these are concepts that are already familiar to them at their age. In addition to teaching children, the parents can also be made aware about gender stereotypes and their effects on society, and in turn be able to teach their own children in more in-depth ways.
Thesis (Bachelor of Fine Arts in Visual Communication)--University of the Philippines Diliman
Bibliography : unnumbered leaves
Keywords: Gender identity -- Philippines; Clothing and dress -- Philippines